Competency Based Medical Education: Integrating two subjects- Physiology of Infancy - Mahajan, Aarti Sood; Mahajan, Akanksha (Journal of Bangladesh Society of Physiologist, 2025)
Infancy reflects a multisystem physiological transition from a dependent foetus to a newborn to a one-year-old child. This is a one-of-a-kind review of literature that is helpful for both medical graduates in concordance with the curriculum outlined by the National Medical Commission’s Competency Based Medical Education in India and for physicians to keep updated about infantile physiology. An in-depth review of literature shows a gradual transition in the physiology of different organ systems with unidirectional anatomical maturation. The respiratory system is characterised by increasing number of alveoli, diaphragm dominance, compliant chest wall, narrow compressible airway and periodic pattern of breathing. The cardiovascular physiology shifts to a left dominant system upon birth. Fetal hemoglobin gradually diminishes allowing greater unloading of oxygen at tissue level. The glomerular filtration, tubular concentration, gastric and hepatic enzyme secretion improves over the next 12-24 months. Infantile skin performs critical thermoregulation and there is evolution of adaptive immunity. There is substantial growth and acquisition of new developmental milestones with progressive neuronal myelination. The hypothalamic pituitary axis is established in infancy, responsible for the interplay of hormones. The review is a novel attempt to highlight marked functional and anatomical changes seen in all organ systems during first year. J Bangladesh Soc Physiol 2024;19(1): 35-45